PENGARUH KECERDASAN INTELEKTUAL TERHADAP KUALITAS AUDIT DENGAN INDEPENDENSI AUDITOR SEBAGAI PEMODERASI (Studi Empiris pada Auditor KAP di Semarang) - Faizah Nur Oktavianna; Sudarno Sudarno (Diponegoro Journal of Accounting, 2020)
This study aims to analyze the effect of intellectual intelligence on audit quality by moderating auditor independence. This research was conducted on auditors working at the Semarang Public Accountant Office. There are two hypotheses in this study, including the influence of intellectual intelligence on audit quality and auditor independence moderates the influence of intellectual intelligence on audit quality. This study uses primary data obtained from the results of distributing questionnaires at the Semarang Public Accountant Office. The sampling method in this study is random sampling. This study uses a moderating regression analysis technique with a test of the absolute value difference. The result of this study indicate that the intellectual intelligence has a positive effect on audit quality. The result of the study shows that auditor independence has a positive effect to moderate the influence of intellectual intelligence on audit quality.